2000
DOI: 10.1023/a:1008368319526
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable analysis of prognostic factors for toxicity and survival for patients enrolled in phase I clinical trials

Abstract: Subgroups with different survival expectancy can be identified among patients who are eligible for phase I clinical trials. If confirmed, the proposed prognostic model may be useful for therapeutic decision making in palliative oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
109
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 21 publications
8
109
3
Order By: Relevance
“…Another study, which analysed 154 patients over an 8-year period, identified two independent risk factors, namely LDH 4600 IU and PS 41, which were correlated with a shorter 90-day OS for patients with both factors. The authors recommended that patients with these risk factors should not participate in a phase I trial (Bachelot et al, 2000). Interestingly, this study also revealed that patients X65 years had a significantly better OS than younger patients in keeping with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Another study, which analysed 154 patients over an 8-year period, identified two independent risk factors, namely LDH 4600 IU and PS 41, which were correlated with a shorter 90-day OS for patients with both factors. The authors recommended that patients with these risk factors should not participate in a phase I trial (Bachelot et al, 2000). Interestingly, this study also revealed that patients X65 years had a significantly better OS than younger patients in keeping with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…cyclophosphamide, methotrexate and infusional 5-FU; 5-FU, folinic acid and interferon). Subanalysis of response rates in the phase I studies of novel CT drugs, excluding these two trials, still showed a partial response rate of 10.3%, which is higher than many previous reports (Estey et al, 1986;Decoster et al, 1990;Bachelot et al, 2000;Sekine et al, 2002). Several of these drugs were new selective topoisomerase inhibitors and would be predicted to have antitumour activity.…”
Section: Discussionmentioning
confidence: 67%
“…Despite the emphasis on evaluation of side effects, and determination of a maximum tolerated dose (MTD), tumour responses remain an important secondary end point. Reported response rates for phase I trials are generally between 1 and 10% (Estey et al, 1986;Decoster et al, 1990;Bachelot et al, 2000) with most responses seen at 80 -120% of the recommended phase II dose (Von Hoff and Turner, 1991). Cytotoxic drugs that do not show antitumour activity in phase I trials rarely undergo further evaluation (Von Hoff and Turner, 1991;American Society of Clinical Oncology, 1997;Sekine et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For these patient-subjects, there is generally little hope left for remission of disease. Phase I oncology research often involves measurement of pharmacokinetics as part of the assessment of the dosage effects, and in addition, trials of molecularly targeted agents may measure specific biochemical parameters relevant to the action of the drug, such as metabolite levels that indicate whether the specific drug effect has been achieved on a molecular level (29,30). Phase I research for new chemotherapeutic agents is often conducted with a dose-escalation design, whereby the first patient-subjects receive low doses of the new agent, and dosage is progressively increased as new patients are enrolled (31).…”
Section: Fertility and Sterilitymentioning
confidence: 99%